Agro-input dealers' perspectives on the designof a certiﬁcation scheme for pesticide riskreduction - Tambo, Justice A; Holmes, Keith; Aliamo, Caroline; Mbugua, Fredrick; Alokit, Christine; Muzira, Fred; Byamugisha, Andrew; Mwambu, Paul (John Wiley and Sons Inc, 2024)
BACKGROUND: While pesticides are essential for crop protection and food security, they pose serious risks to human health and the environment. Agro‐input dealers can play an important role in mitigating pesticide risks, given that they are a major source of pesticides and plant health information for many developing‐country farmers. In this article, we assess the willingness of agro‐input dealers to offer integrated pest management‐based advisory services and promote pesticide risk reduction through a voluntary certification scheme. RESULTS: Using survey data from 557 agro‐input dealers in Uganda and a discrete choice experiment, we find that the proposed certification scheme is significantly valued by agro‐input dealers, particularly for its potential to provide training opportunities and ensure safety to human health and the environment. Agro‐input dealers have a positive attitude towards a certification scheme that restricts the sale of high‐risk pesticide products, especially if it stimulates additional income‐generating opportunities. Further analysis shows that preferences for voluntary certification attributes are influenced by certification experience, agro‐dealership experience, business ownership status and incidence of acute pesticide poisoning. CONCLUSION: The study findings demonstrate that agro‐input dealers are conscious of pesticide risks to human and environmental health and are keen to participate in a certification scheme promoting safer plant protection products. © 2024 The Author(s). Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. AGRICOLA